LITERATUR REVIEW: HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN DIARE PADA ANAK: LITERATUR REVIEW: HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN DIARE PADA ANAK - Ibad, Musyfiqul; Kusyani, Asri; Santoso, Shelfi Dwi Retnani Putri; Effendi, Zainudin (LPPM STIKes Bahrul Ulum Jombang, 2021)
Diarrheal diseases are high and often fall into KLB categories in various parts of Indonesia. According to who (2017) data on world diarrhea events still 1.7 billion a year, the cause of death in both children-children. Data on the incidence of diarrheal diseases in Indonesia reach 6 million cases annually, with 36 deaths ata value of CFR 4.76%. Kemenkes RI (2018). The purpose of this study is to identify the environmental sanitation connections with the occurrence of diarrhea in children. The study used a textbook review method based on the journal search process for the full text article from a database on Google scholar, scient direct, ebsco, proquest, and springer. Taken, published in 2015-2020, the journal has a total of 10. According to the results of this study, there are 2 related environmental sanitation links to the incidence of diarrhoea in children, and according to the provision of clean water, there are 7 related journals and according to the disposal of human waste. Good environmental conditions are an important effort to prevent diarrhoea in children.